McGlynn Versus Aveling: A Comparison of Translation Strategies Used in Sapardi Djoko Damono’s Poems - Muhammad Aditya Ramadhan (Passage, 2016)
Translation has been widely recognized as a way to connect cultures among the world through literary works. However, translating literary works is not an easy task, especially poetry. This research entitled “McGlynn versus Aveling: A Comparison of Translation Strategies Used in Sapardi Djoko Damono’s Poems” aims to analyse strategies of translating poetry proposed by Andre Lefevere, and how they can impact the translation results of five poems by two different translators: John McGlynn and Harry Aveling. The poems were collected from three books: Black Magic Rain, Contemporary Indonesian Poetry, and Before Dawn. A descriptive analysis method was employed in this study alongside a little approach of a case study. The findings showed that the most frequent strategy used by both translators was Literal Translation. Strategies used by both translators also affect the lexical thematic, visual, and rhythmic acoustic dimension of the poems indirectly.Keywords: Translation, Poetry, Strategies